2012
DOI: 10.1073/pnas.1121249109
|View full text |Cite
|
Sign up to set email alerts
|

Factors underlying variable DNA methylation in a human community cohort

Abstract: Epigenetics is emerging as an attractive mechanism to explain the persistent genomic embedding of early-life experiences. Tightly linked to chromatin, which packages DNA into chromosomes, epigenetic marks primarily serve to regulate the activity of genes. DNA methylation is the most accessible and characterized component of the many chromatin marks that constitute the epigenome, making it an ideal target for epigenetic studies in human populations. Here, using peripheral blood mononuclear cells collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
368
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 425 publications
(404 citation statements)
references
References 52 publications
32
368
2
2
Order By: Relevance
“…22 An increasing number of reports have further proposed that the methylome-transcriptome relationship cannot be represented by a simple model when considering large, high quality datasets. 10,21,23,36,37 In these studies, positive and negative correlations between methylation alterations and transcriptome changes were found only for a minority of CpGs. It was also suggested that the relationship depends on the CpG-content of the promoter region.…”
Section: Discussionmentioning
confidence: 89%
“…22 An increasing number of reports have further proposed that the methylome-transcriptome relationship cannot be represented by a simple model when considering large, high quality datasets. 10,21,23,36,37 In these studies, positive and negative correlations between methylation alterations and transcriptome changes were found only for a minority of CpGs. It was also suggested that the relationship depends on the CpG-content of the promoter region.…”
Section: Discussionmentioning
confidence: 89%
“…Smoking‐associated DNA methylation changes have also been found in genes involved in inflammatory networks, important candidates in the risk of age‐related diseases such as heart disease and stroke (Breitling et al ., 2012; Dogan et al ., 2014). Other environmental influences, such as abuse or adversities in childhood, have also been linked to stable DNA methylation differences that persist into adulthood (Meaney, 2010; Essex et al ., 2011; Borghol et al ., 2012; Lam et al ., 2012; Klengel et al ., 2013). The accumulation of these environmental exposures, either shared or unshared across individuals, would then contribute to epigenetic change with age.…”
Section: Epigenetic Drift Vs the Epigenetic Clock: Two Phenomena Undmentioning
confidence: 99%
“…It is important to note that many of the studies discussed in this review have not been adjusted for differences in cellular composition with age. Therefore, tissue‐specific epigenetic clock sites in some of these studies may not be accurate; however, the overall patterns of DNA methylation change with age have been validated in studies that did correct for cellular composition (Lam et al ., 2012; Lister et al ., 2013; Jaffe & Irizarry, 2014). …”
Section: Considerations For Studies Of Epigenetics and Agingmentioning
confidence: 99%
See 2 more Smart Citations